SIMASET SIMASET PERANGKAT TEKNOLOGI INFORMASI PADA KANTOR KESEHATAN PELABUHAN KELAS III JAMBI: Assets;MYSQL;Maintenance;Information Technology Devices;System. - Wahyuning Astuti, Reny; Riswan; Bayu Rasul Liyanda, Ragil (FORTECH (Journal of Information Technology), 2021)
An organization or company certainly has assets to support its operational activities, so it is very important to maintain the assets themselves. Not maintaining assets and asset data can be an important problem for the organization or company. This asset maintenance system aims to facilitate the maintenance of asset data, especially at the Jambi Class III Port Health Office. The Jambi Class III Health Office is a Technical Implementation Unit within the Ministry of Health which is under and responsible to the Directorate General of Disease Prevention and Control. Asset maintenance in the office still uses the manual method, namely the person in charge of the room comes directly to make a request for repairs, making it difficult for officers to maintain these assets. To overcome this problem, we need a form of asset maintenance system that can assist in the repair request process. Making this application is done by collecting data, system planning, system analysis, system design and database. The database used is MySQL. The input requirements for the Information Technology Equipment Asset Maintenance System are asset data, room data, and work area data. The process requirements needed are: Login process, request process, and input, update, and delete processes. The output data produced is in the form of information that will be attached, including: the request report is approved, and the request data report is rejected. The purpose of making this thesis is the creation of a Web-Based Information Technology Device Asset Maintenance System. With the existence of a new system that has been designed and created by researchers, it can help facilitate the parties involved in maintaining information technology equipment assets.